Clinical and CT Features, Clinical Management, and Decision on Sport Eligibility of Professional Athletes with Congenital Coronary Anomalies: A Case Series Study - Gianluca Guarnieri; Edoardo Conte; Davide Marchetti; Matteo Schillaci; Eleonora Melotti; Andrea Provera; Marco Doldi; Maria Rosaria Squeo; Antonio Pelliccia; Viviana Maestrini; Daniele Andreini (Journal of Cardiovascular Development and Disease)
Background: Congenital coronary artery anomalies (CAAs) are a significant cause of sudden cardiac death and a key factor in determining athletes’ eligibility for competitive sports. Their prevalence varies with diagnostic modalities and may present as asymptomatic or with life-threatening ischemic or arrhythmic events. This case series highlights the diverse manifestations of CAAs and the clinical approaches used to determine sports eligibility. Cases description: Five competitive athletes with different CAAs are presented. These cases include anomalous coronary origins, intramyocardial bridges, and coronary fistulas. Diagnostic tools, including coronary CT angiography (CCTA), cardiac magnetic resonance imaging (CMR), and stress tests, were essential in evaluating these anomalies and determining treatment strategies. In some cases, such as intramyocardial bridges, surgical intervention was necessary, while others required conservative management or exclusion from competitive sports. Conclusions: CAAs require individualized care based on risk stratification through advanced imaging techniques and functional assessment. Surgical interventions are reserved for high-risk anomalies, while others may be managed conservatively. Early detection and tailored management are crucial for ensuring athletes’ safety, and ongoing research is needed to optimize long-term outcomes.